A semi-synthetic whole parasite vaccine designed to protect against blood stage malaria. (15th October 2016) - Giddam, Ashwini Kumar; Reiman, Jennifer M.; Zaman, Mehfuz; Skwarczynski, Mariusz; Toth, Istvan; Good, Michael F.
Graphical abstract: Abstract: Although attenuated malaria parasitized red blood cells (pRBCs) are promising vaccine candidates, their application in humans may be restricted for ethical and regulatory reasons. Therefore, we developed an organic microparticle-based delivery platform as a whole parasite malaria-antigen carrier to mimic pRBCs. Killed blood stage parasites were encapsulated within liposomes that are targeted to antigen presenting cells (APCs). Mannosylated lipid core peptides (MLCPs) were used as targeting ligands for the liposome-encapsulated parasite antigens. MLCP-liposomes, but not unmannosylated liposomes, were taken-up efficiently by APCs which then significantly upregulated expression of MHC-ll and costimulatory molecules, CD80 and CD86. Two such vaccines using rodent model systems were constructed – one with Plasmodium chabaudi and the other with P. yoelii . MLCP-liposome vaccines were able to control the parasite burden and extended the survival of mice. Thus, we have demonstrated an alternative delivery system to attenuated pRBCs with similar vaccine efficacy and added clinical advantages. Such liposomes are promising candidates for a human malaria vaccine. Statement of Significance: Attenuated whole parasite-based vaccines, by incorporating all parasite antigens, are very promising candidates, but issues relating to production, storage and safety concerns are significantly slowing their development. We therefore developed a semi-synthetic whole parasite malaria vaccine that is easily manufactured and stored. Two such prototype vaccines (a P. chabaudi and a P. yoelii vaccine) have been constructed. They are non-infectious, highly immunogenic and give good protection profiles. This semi-synthetic delivery platform is an exciting strategy to accelerate the development of a licensed malaria vaccine. Moreover, this strategy can be potentially applied to a wide range of pathogens.